1990
DOI: 10.1097/00001888-199009000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric impairment in medical students

Abstract: This retrospective study of 217 medical students (at one school over an eight-year period) who had sought psychiatric consultation and treatment was designed to verify earlier findings about medical students' psychiatric impairment and to investigate other, more recently highlighted issues. The authors hypothesized that (1) more of the women would be seen for psychiatric consultation; (2) overall, the problems and diagnoses of the students would differ according to gender and academic class; (3) the women woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
0
11
0
5
Order By: Relevance
“…Breaking the help-seeking process down into stages revealed that women were more likely than men to recognize and label nonspecific feelings of distress as emotional problems. Other studies have documented similar findings in medical students (Dickstein, Stephenson, & Hinz, 1990), college students (Gim, Atkinson, & Whiteley, 1990;Leong & Zachar, 1999;M. O'Neil, Lancee, & Freeman, 1985), university employees, the majority of whom were faculty (Carpenter & Addis, 2000), and members of a Canadian community (D'Arcy & Schmitz, 1979).…”
Section: Are Men Less Likely Than Women To Seek Professional Help?mentioning
confidence: 53%
“…Breaking the help-seeking process down into stages revealed that women were more likely than men to recognize and label nonspecific feelings of distress as emotional problems. Other studies have documented similar findings in medical students (Dickstein, Stephenson, & Hinz, 1990), college students (Gim, Atkinson, & Whiteley, 1990;Leong & Zachar, 1999;M. O'Neil, Lancee, & Freeman, 1985), university employees, the majority of whom were faculty (Carpenter & Addis, 2000), and members of a Canadian community (D'Arcy & Schmitz, 1979).…”
Section: Are Men Less Likely Than Women To Seek Professional Help?mentioning
confidence: 53%
“…A literatura mostra uma tendência a escores mais altos em escalas de depressão e ansiedade, e escores mais baixos em escalas de QV quando respondidos pelo sexo feminino. Isso pode ser explicado por um maior cuidado das mulheres nas respostas, por apresentarem uma visão mais crítica do tema, por dedicarem maiores cuidados e terem maiores preocupações com a sua saúde e com a dos outros 27,28 . Neste estudo, não foram encontradas diferenças nos valores atribuídos à QV na autoavaliação e nos escores do WHOQOL entre os sexos.…”
Section: Resultsunclassified
“…A estratificação do grupo estudado resultou em um número de indivíduos pequeno por grupo, o que tornou mais difícil encontrar diferenças significativas entre sexo, como demonstrado em estudos anteriores sobre qualidade de vida, nos quais o grupo de estudantes do sexo feminino apresentou menores escores nos quatro domínios do WHOQOL. A literatura demonstra, em muitos estudos, que em questionários subjetivos sobre saúde física e mental as mulheres têm escores menores que os homens, tendo em vista que o grupo masculino, em geral, mantém conduta de risco em relação à saúde 5,27 . O fato de não ter sido encontrada diferença entre o grupo de residentes do sexo feminino e o do sexo masculino pode ainda ser decorrente da cobrança no ambiente de trabalho, que modifica a postura das mulheres residentes em relação à sua saúde e à qualidade de vida.…”
Section: Tabela 2 Escores Dos Domínios Do Whoqol -Abreviado Nos Médicunclassified
“…C. Clark & Zeldow, 1988;Dickstein, Stephenson, & Hinz, 1990;Helmers, Danoff, Steinert, Leyton, & Young, 1997;Roberts, 2010). It is well known that many students experience stress as part of a medical education process (Finkelstein et al, 2007;Henning et al, 1998;Schmitter et al, 2008), and stress has been recognized to have a negative effect on academic performance (Spiegel et al, 1986), health and psychological well-being (Helmers et al, 1997).…”
Section: Psychological Distress During the Process Of Medical Educationmentioning
confidence: 99%
“…While there is a limited understanding of psychological distress among PA students (M. H. Brown, 2004;Childers et al, 2012;Glicken & Gray, 1993;Kuhn et al, 2005;O'Brien et al, 2012), there is an abundance of literature regarding psychological distress among other health professions students as previously noted (Cardall et al, 2008; D. C. Clark & Zeldow, 1988;Dickstein et al, 1990;Helmers et al, 1997;Roberts, 2010). PA student participants in this study describe similar stressors, and while questions about anxiety and depression were not specifically asked during the focus group sessions, the tenor of the conversations suggests the likelihood that these psychological challenges may exist within this collective group of students.…”
Section: Burnoutmentioning
confidence: 99%